Oceania in the Desert: A QuantCrit Analysis of the (Under)Counting of Native Hawaiian and Pacific Islander Students at an AANAPISI-HSI - Espinoza, Kristine Jan Cruz; Rincón, Blanca E.; Drake, Brent M.; Harbin, J. Judd; Ethelbah, Kyle K. (Journal of research on educational effectiveness, 2025)
Most education research uses the National Center for Education Statistics (NCES) Integrated Postsecondary Education Data System (IPEDS), often leaving the logic undergirding the IPEDS racial classification system (i.e., categorization and counting) unquestioned. Framed by Quantitative Critical Race Theory (QuantCrit) principles, this research demonstrates how the NCES IPEDS racial classification misrepresents and undercounts students. Specifically, we show how IPEDS guidance around racial classification misrepresents the number of Asian American, Native Hawaiian, and Pacific Islander (AA&NHPI) undergraduates, with particular attention to NHPI students, at a single institution. We show the ways in which IPEDS logic leads to undercounting, namely that, based on the NCES IPEDS racial classification system, most undergraduates identifying as NHPI are classified as Two or More Races and Hispanic or Latino. A similar pattern of suppression is found to varying degrees for students identifying as American Indian or Alaska Native, Asian, and Black or African American. Our findings complicate the taken-for-granted nature of IPEDS racial classification and have implications for serving racially minoritized student groups and for institutions that may qualify as enrollment-based Minority-Serving Institutions.